Eksplorasi Transformasi Simbolik Gajah Oling Dalam Penciptaan Busana Ready to Wear Berbasis Budaya Banyuwangi - Rizka Sarah Heydarina Fathima Ahsan; Sri Eko Puji Rahayu; Asriana Kibtiyah (BAJU: Journal of Fashion and Textile Design Unesa, 2025)
The purpose of the research is to create a ready-to-wear fashion design that integrates Banyuwangi cultural values through the transformation of the Oling Elephant Batik motif and the anatomical character of the elephant into a contemporary fashion silhouette. The methods used with the stages of research on the creation of works include pre-design, design, realization, and presentation. In the pre-design stage, an exploration of the study of the philosophy of the Elephant Oling, analysis of elephant anatomy as a source of shape, and the selection of materials and textile techniques. The planning stage produces alternative sketches and is created at the embodiment stage covering patterns, material cuts, sewing and finishing. The results of the study show that the integration of cultural values, shape transformation and textile manipulation can produce ready-to-wear clothing that is aesthetic, functional and has narrative power. This research affirms the potential of contemporary fashion as a medium of cultural revitalization and offers a new model of approach in symbolic-based design. Further research is recommended to examine user responses and the potential for collection development at a production scale.